California Democratic Council Statewide Convention at Hacienda Inn - Watkins, Howard::::::::: (1982)
Lia Triff Belli, Fresno Mayor Dan Whitehurst speaking with U.S. Senator Ted Kennedy, ? Convention Banner: We the people action for the '80's"